대테러전략의 게임이론적 분석 - 이상훈 (13234, 2013)
This paper analyzes a situation where multiple targets are exposed to a potential terrorist attack. The probability of an attack is determined endogenously in a game where a terrorist chooses the target while the targets independently determine the level